2023
DOI: 10.31234/osf.io/z38u6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surprisal does not explain syntactic disambiguation difficulty: evidence from a large-scale benchmark

Abstract: Prediction has been proposed as an overarching principle that explains human information processing in language and beyond. To what degree can processing difficulty in syntactically complex sentences - one of the major concerns of psycholinguistics - be explained by predictability, as estimated using computational language models? A precise, quantitative test of this question requires a much larger scale data collection effort than has been done in the past. We present the Syntactic Ambiguity Processing Benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 78 publications
3
13
0
Order By: Relevance
“…Schijndel & Linzen [13] generated a linear regression model of reading times as a function of surprisal, and used it to predict garden-path effects. Similar to us, they observed that surprisal underestimates the garden-path effects, but different from us, they could not distinguish between the NP/S and NP/Z sentences [13,26,27]. Although statistical tests are not quoted in [13], our model clearly outperforms the results obtained from surprisal and our predictions for NP/Z sentences are significantly higher than for NP/S sentences, see table 9.…”
Section: (B) Comparison With Surprisalsupporting
confidence: 63%
See 2 more Smart Citations
“…Schijndel & Linzen [13] generated a linear regression model of reading times as a function of surprisal, and used it to predict garden-path effects. Similar to us, they observed that surprisal underestimates the garden-path effects, but different from us, they could not distinguish between the NP/S and NP/Z sentences [13,26,27]. Although statistical tests are not quoted in [13], our model clearly outperforms the results obtained from surprisal and our predictions for NP/Z sentences are significantly higher than for NP/S sentences, see table 9.…”
Section: (B) Comparison With Surprisalsupporting
confidence: 63%
“…Indeed, the reading times used for doing the linear regression were only averages of reading times across different sentences and different participants; and this caused discrepancies in our results. We plan to use more detailed datasets such as a recent one released in [27]…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do agree with Houghton et al that it can be useful to compare language in DNNs and humans to explore the capacities of DNNs that do not have any language-specific learning mechanism. But at present, not only do the learning objectives and learning constraints seem wildly different in the two systems, but also, the performance of fully trained models "sharply diverges" from humans in controlled experiments (Huang et al, 2023).…”
Section: R62 Marketing and (Mis)characterizing Research Findingsmentioning
confidence: 99%
“…In other words, although prior evidence favors an inferential (rather than a procedural preactivation-based) interpretation of predictability effects and thus implicates inference as a key “causal bottleneck” on processing demand, the present finding of surprisal-independent frequency effects could suggest limits on the scope of this bottleneck: frequency (and thus plausibly lexical retrieval) also plays a large and surprisal-independent role in determining how long participants spend reading words. Given the remarkable success of surprisal in accounting for a range of language processing phenomena across diverse experimental measures (Demberg & Keller, 2008 ; Frank & Bod, 2011 ; Frank et al, 2015 ; Heilbron et al, 2022 ; Hoover et al, 2023 ; Lopopolo et al, 2017 ; Roark et al, 2009 ; Shain et al, 2020 , in press ; Smith & Levy, 2013 ; van Schijndel & Schuler, 2015 ; Wilcox et al, 2020 ), discoveries highlighting the explanatory limits of surprisal offer opportunities for new insights into the mechanisms and representational format of incremental meaning construction during language comprehension (e.g., Huang et al, 2023 ; van Schijndel & Linzen, 2021 ).…”
Section: Discussionmentioning
confidence: 99%